A new Lamellibrachia species and confirmed range extension for Lamellibrachia barhami (Siboglinidae, Annelida) from Costa Rica methane seeps - Mccowin, Marina F.; Rouse, Greg W. (Zootaxa, 2018)
Lamellibrachia Webb, 1969 has eight currently recognized species reported from chemosynthetic environments in the Pacific, Atlantic, and Mediterranean. Of these, Lamellibrachia barhami Webb, 1969 has been reported in the eastern Pacific from Canada to Costa Rica. In this study, phylogenetic analyses of Lamellibrachia tubeworms sampled from the Costa Rica margin confirm the large geographic range of L. barhami and reveal a new Lamellibrachia species from a single methane seep between 999 and 1,040 meters. Lamellibrachia donwalshi sp. nov. differs genetically and morphologically from all congeneric species. Despite its geographic proximity to the eastern Pacific L. barhami, L. donwalshi sp. nov. formed a clade with Atlantic and Mediterranean Lamellibrachia species. This suggests a vicariant event may have occurred after an Atlantic radiation of Lamellibrachia.